Pengaruh Lingkungan Kerja, Stres Kerja Dan Motivasi Terhadap Produktivitas Karyawan (Studi pada PT Karyamega Putra Mandiri) - Afiandi, Dian; Rizal, Mohammad; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research seeks to analyze the influence of the work environment, job stress, and motivation on employee productivity in Verpak SKT division at PT Karyamega Putra Mandiri. A quantitative approach was employed, using non-probability sampling to select 72 employees as respondents. Data were analyzed using multiple linear regression analysis with the assistance of SPSS 25 software. The hypothesis test was performed the F-test to evaluate simultaneous effects and partial effects use t-test. The study findings reveal that simultaneously, the work environment, job stress, and motivation have a significant influence on employee productivity. Partially, each variable work environment, job stress, and motivation also significantly affects employee productivity. These findings emphasize the importance of creating a conducive work environment, effectively managing job stress, and providing appropriate motivation to enhance employee productivity. Keywords: Work Environment, Job Stress, Motivation, Employee Productivity